The oncogenic roles of JC polyomavirus in cancer - Zheng, Hua-chuan; Xue, Hang; Zhang, Cong-yu (Frontiers in Oncology, 2022)
John Cunningham polyomavirus (JCPyV) belongs to the human non-enveloped polyomavirus family in the combination of SV40 and BK viruses. Based on alternative splicing, the early region encodes the large and small T antigens, while the late region encodes the capsid structural proteins (VP1, VP2, and VP3) and the agnoprotein, a small regulatory element. The regulatory transcription factors for JCPyV include Sp1, TCF-4, DDX1, YB-1, LCP-1, Purα, GF-1, and NF-1 under the stimulation of cytokines (TGF-β1 and TNF-α). JCPyV enters tonsillar tissue through the intake of raw sewage, inhalation of air droplets, or parent-to-child transmission. It persists quiescently in lymphoid and renal tissues during latency. The distinct distribution of its receptors (α-2, 6-linked sialic acid, non-sialylated glycosaminoglycans, and serotonin) determines the different infection capabilities for the surface capsid of JCPyV virions, and JCPyV entry is mediated by clathrin-mediated endocytosis. SF2/ASF downregulates the transcription and alternative splicing of JCPyV genes, while either LIP induced the degradation of T antigen. In permissive cells, JCPyV undergoes lytic proliferation and causes progressive multifocal leukoencephalopathy (PML), while its DNA is inserted into genomic DNA and leads to carcinogenesis. It is detectable in human tissues by general, nested, real-time and in situ PCR, in situ hybridization and immunohistochemistry. T antigen targets p53, β-catenin, IRS, Rb, TGF-β1, PI3K/Akt and AMPK signal pathways primarily in cancer cells. Intracranial injection of T antigen into animals results in neural tumors, and transgenic mice develop neural tumors, lens tumors, breast cancer, and gastroenterological tumors. Additionally, JCPyV DNA and its encoded products can be detected in the brain tissues of PML patients and brain, oral, esophageal, gastric, colorectal, breast, cervical, pancreatic, and hepatocellular cancer tissues. Therefore, JCPyV might represent an etiological risk factor for carcinogenesis and should be evaluated for early prevention, diagnosis, and treatment of cancer.